The Problem of Methodological Fixation of Analytical Jurisprudence - D. G. Alova; A. A. Iljushkin (Теоретическая и прикладная юриспруденция)
The article examines the problem of the fixation of analytical jurisprudence on conceptual analysis of legal concepts. The first part of the work is devoted to the consideration of the latter as a heterogeneous method of analytical jurisprudence, in contrast to its limited understanding that prevails in current jurisprudence. The second and third parts trace the genesis of analytical jurisprudence from analytic philosophy. Based on the thoughts of Dagfinn Follesdal, an analogy is drawn between the paths of analytical jurisprudence and analytic philosophy. It is concluded that analytical jurisprudence in the doctrinal sense will go through a path of separation from conceptual analysis, which analytic philosophy has already passed. The fourth part of the article examines the foundations of analytical jurisprudence in the form of the legal theory of Herbert Hart, who, being the founder of analytical jurisprudence, defined the entire subsequent analytic tradition in jurisprudence in such a way that its focus is not limited only to issues of legal language. Based on this, it is concluded that initially in analytical jurisprudence it was not strict conceptual analysis that prevailed, but conceptual logic, which made it possible to develop legal teaching in a practical way and only later gave rise to linguistic studies of law. The thesis is brought up for discussion that analytical jurisprudence, like analytic philosophy in general, does without strict conceptual analysis for its constitution. It is enough for her to have more general ideas about proving and justifying her theses. In addition, in the fifth part of the article, parallels are drawn between conceptual analysis as a method of analytic philosophy and the concept of the hermeneutic circle, traditionally inherent in continental philosophy. The main thesis of the article submitted for discussion is the assertion that the methodological fixation of analytical jurisprudence, which has become established as a relevant research tradition, must be overcome, since it is justified exclusively discursively, and not on the basis of sound reflection.